2021
DOI: 10.1371/journal.pone.0259701
|View full text |Cite
|
Sign up to set email alerts
|

Optimal management of peripancreatic fluid collection with postoperative pancreatic fistula after distal pancreatectomy: Significance of computed tomography values for predicting fluid infection

Abstract: Peripancreatic fluid collections have been observed in most patients with postoperative pancreatic fistula after distal pancreatectomy; however, optimal management remains unclear. This study aimed to evaluate the management and outcomes of patients with postoperative pancreatic fistula and verify the significance of computed tomography values for predicting peripancreatic fluid infections after distal pancreatectomy. We retrospectively investigated 259 consecutive patients who underwent distal pancreatectomy.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Although various reports have evaluated the optimal pancreatic stump closure method for POPF reduction, no consensus has been established, and further studies are needed to identify a closure method that reduces the incidence of CR-POPF. Furthermore, based on our previous report [ 24 ], a consideration from the perspectives of intraoperative and postoperative management indicated that the inappropriate drainage tube placement and/or number of drain tubes in our department may have increased the number of cases requiring additional intervention and may have also resulted in excessive use of postoperative therapeutic antibiotics. If the drainage is appropriate, the drain can be removed at an early stage; furthermore, if the indication for therapeutic antibiotic use is judged more strictly, then it would not result in Grade B CR-POPF, and there may be more cases that would heal with a biochemical leak (BL).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although various reports have evaluated the optimal pancreatic stump closure method for POPF reduction, no consensus has been established, and further studies are needed to identify a closure method that reduces the incidence of CR-POPF. Furthermore, based on our previous report [ 24 ], a consideration from the perspectives of intraoperative and postoperative management indicated that the inappropriate drainage tube placement and/or number of drain tubes in our department may have increased the number of cases requiring additional intervention and may have also resulted in excessive use of postoperative therapeutic antibiotics. If the drainage is appropriate, the drain can be removed at an early stage; furthermore, if the indication for therapeutic antibiotic use is judged more strictly, then it would not result in Grade B CR-POPF, and there may be more cases that would heal with a biochemical leak (BL).…”
Section: Discussionmentioning
confidence: 99%
“…The basic postoperative and POPF management used in this study has been described in our previous report [ 24 ]. Prophylactic antibiotics (second-generation cephalosporin) were administered through POD 2.…”
Section: Methodsmentioning
confidence: 99%
“…The patients who underwent L-DP were managed postoperatively as reported. 12 The administration of prophylactic antibiotics was routinely continued through the postoperative day (POD) 2. Prophylactic somatostatin analogs were not routinely used.…”
Section: Postoperative Management and Evaluation Of Postoperative Pan...mentioning
confidence: 99%